Merging the Boundaries of Religion, Science, and Philosophy for Pedagogical Effectiveness - Chackalackal, Saju (Journal of Dharma, 2015)
Religion, science, and philosophy, as they have evolved their independent domains over the years, have developed autonomously and, hence, have made significant impact upon human life. Each of these has continuously striven to dominate humanity at different periods in the development of human civilizations. In the course of time, however, as religion began to take control over human life, and as it realized the fact that independent operations of philosophy and sciences can result in difficult situations for matters religious (especially due to the scientific and critical approaches that these disciplines adopted about those aspects of religion which did not match with the explicit pronouncements made by philosophers and scientists). As religious leaders started to exercise undue influence (and many a time unchallengeable powers, due to political patronage) upon philosophical and scientific programmes and processes, there arose suspicion about religion and religious practices in the minds of both philosophers and scientists. This gradually led to the escalation of relationship among these three vital domains of human existence; in fact, it is this mutual distancing that played havoc upon human creativity, especially as each of these disciplines started to claim complete autonomy from each other, and began to function to the mutual exclusion and, sometimes, with mistrust and disrespect for the methods adopted by each other.